Transcriptional condensates: a blessing or a curse for gene regulation? - Stortz, Martin Dario (2024)
Whether phase-separation is involved in the organization of the transcriptional machinery and if it aidsor inhibits the transcriptional process is a matter of intense debate. In this Mini Review, we will coverthe current knowledge regarding the role of transcriptional condensates on gene expressionregulation. We will summarize the latest discoveries on the relationship between condensateformation, genome organization, and transcriptional activity, focusing on the strengths andweaknesses of the experimental approaches used to interrogate these aspects of transcription inliving cells. Finally, we will discuss the challenges for future research.